2002
DOI: 10.1038/sj.bjc.6600089
|View full text |Cite
|
Sign up to set email alerts
|

Prerequisites for effective adenovirus mediated gene therapy of colorectal liver metastases in the rat using an intracellular neutralizing antibody fragment to p21-Ras

Abstract: Ras mutations are present in 40 -50% of colorectal cancers. Inactivating this oncogene may therefore reduce proliferation capacity. In order to target ras we studied the transduction efficacy and anti tumour activity of an adenoviral vector expressing an intracellular, neutralizing single chain antibody to p21-ras (Y28). In in vitro studies transfection levels of the K-ras mutated rat colon carcinoma cell line CC531 were studied using the LacZ marker gene. In our in vivo liver metastases model different routes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…When adenoviruses are used in IHP it has been demonstrated that high transduction percentages can be achieved (de Roos et al, 1997;Drazan et al, 1995;van Etten et al, 2004a;van Etten et al, 2002b). Regarding toxicity following IHP a maximum transient weight loss of 10% was observed, which could not be related to the viral vector as similar weight loss was observed upon sham IHP (van Etten et al , 2002b). Drazan et al, studied the influence of adenovirus mediate gene transfer on hepatic function in further detail by means histological, biochemical and functional studies (Drazan et al, 1995).…”
Section: Hepatocyte-targeted Gene Therapy For Inborn Errors Of Metabomentioning
confidence: 88%
See 3 more Smart Citations
“…When adenoviruses are used in IHP it has been demonstrated that high transduction percentages can be achieved (de Roos et al, 1997;Drazan et al, 1995;van Etten et al, 2004a;van Etten et al, 2002b). Regarding toxicity following IHP a maximum transient weight loss of 10% was observed, which could not be related to the viral vector as similar weight loss was observed upon sham IHP (van Etten et al , 2002b). Drazan et al, studied the influence of adenovirus mediate gene transfer on hepatic function in further detail by means histological, biochemical and functional studies (Drazan et al, 1995).…”
Section: Hepatocyte-targeted Gene Therapy For Inborn Errors Of Metabomentioning
confidence: 88%
“…In an adenovirus based IHP model we are investigating the immune response upon IHP as well. Recently an impaired neutralizing antibody production was observed in rats (van Etten et al, 2004b). Manipulation of adenoviruses to reduce antigenicity is currently performed on a wide scale and this may in combination with local delivery be a future option for repeated delivery thereby offering possible clinical application options.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further proof of this hierarchy of administration methods was provided in an analysis of the administration of armed adenoviral vectors encoding LacZ or anti-p21ras antibody by intratumoural injection, IHP, HAI or intravenous infusion. 80 The model used was hepatic colorectal cancer metastases. The greatest level of infection was provided by intratumoural injection at 5%, with IHP providing 2–3% infection of target cells.…”
Section: Specific Organ Perfusionmentioning
confidence: 99%